From pandemics to artificial intelligence, robots, and transhumanism: New challenges for ethics - Lourdes Velázquez (Bioethics Update, 2022)
The reference to an ontological stable human nature has been considered the foundation of ethics in Western civilization until the last century and a negative appreciation of the artificial was often entailed. Today, the situation has deeply changed and the idea is gaining credit that it is through the progress of science and technology that humankind can really progress both from the material and the moral point of view. In this paper, a positive appreciation of technoscience is expressed but the need of a critical appreciation of its use is also demonstrated through a detailed analysis of certain spectacular advancements of technology (such as medical achievements, artificial intelligence, and robotics). The fact that this progress can be steered only by reference to values that cannot be offered by technoscience is contained in a criticism of transhumanism.